THE PREVALENCE AND IMPACT OF ISOLATED DIASTOLIC HYPERTENSION IN CHILDREN. (June 2022) - Myette, Robert; Obrycki, Lukasz; Litwin, Mieczyslaw; Seeman, Tomas; Feber, Janusz
Abstract : Objective: Isolated systolic (iSH) and combined (SDH) hypertension is associated with increased left ventricular mass index (LVMi). Isolated diastolic hypertension (iDH) is less commonly observed and its impact on LVMi in children is less clear. To analyze the prevalence of iDH in children (1–18 years), and associations between iDH and BMI Z-score (BMIz) and LVMi. Design and method: We enrolled 1971 pediatric patients from 3 academic centres: Ottawa, Canada; Warsaw, Poland; Prague, Czech Republic who were worked up/treated for hypertension. All patients had office and ambulatory blood pressure monitoring (ABPM). Office and ambulatory (daytime, nighttime, 24-hour) iDH was defined as diastolic blood pressure Z-score (DBPz)> 1.65, with systolic BP Z-score (SBPz) < = 1.65. 511/1971 had LVMi (g/m^2.7) adjusted to the 95th percentile (aLVMi) using Khoury et al. Results: The distributions of office BP were: iSH in 28.6%, SDH in 19.4%, iDH in 3.0% and normotension in 49.0%. Children with office iDH had lower aLVMi compared to those with iSH (p = 0.01) or SDH (p = 0.005). Those with iDH also had lower BMIz compared to iSH (p = 0.0004) and SDH (p = 0.007). The distributions of 24-hour ambulatory BP were: iSH in 24.0%, SDH in 15.0%, iDH in 5.0% and normotension in 56%. Daytime iDH was observed in 2.8% and nighttime iDH in 6.8%. Those with daytime (p = 0.003) and nighttime (p = 0.009) iDH had a lower BMIz compared to those with iSH, but there was no difference in BMIz between those with iDH and SDH. Primary hypertension patients with nighttime iDH had lower aLVMi compared to those with nighttime iSH (p = 0.04) or SDH (p = 0.03). There were no other differences in aLVMi between iDH, and iSH or SDH. Conclusions: In summary, the prevalence of office and ambulatory iDH is low (3–5%) in children. Those with iDH appear to have a lower BMIz and aLVMi compared to those with iSH and SDH.